Marker-assisted introgression of wild chromosome segments conferring resistance to fungal foliar diseases into peanut (Arachis hypogaea L.) - Moretzsohn, Márcio de Carvalho; Santos, João Francisco dos; Moraes, Andrea Rocha Almeida; Custódio, Adriana Regina; Michelotto, Marcos Doniseti; Maharjan, Namrata; Leal-Bertioli, Soraya Cristina de Macedo; Godoy, Ignácio José; Bertioli, David John (Frontiers in Plant Science, 2023)
Fungal foliar diseases are important worldwide and can severely affect productivity of the peanut crop. Late leaf spot is the most frequent disease and the major problem of the crop in Brazil and many other tropical countries. Only partial resistance to fungal diseases has been found in cultivated peanut, but high resistances have been described on the secondary gene pool. To overcome the known compatibility barriers for the use of wild species in peanut breeding programs, we used an induced allotetraploid (Arachis stenosperma x A. magna)4x, as donor parent, in a successive backcrossing scheme with the high-yielding Brazilian cultivar IAC OL 4. We used microsatellite markers associated to late leaf spot and rust resistance for foreground selection and high-throughput SNP genotyping for background selection. With these tools, we developed agronomically adapted lines with high cultivated genome recovery, high-yield potential and wild chromosome segments from both A. stenosperma and A. magna conferring high resistance to late leaf spot and rust. These segments include the four previously identified as having QTLs (Quantitative Trait Loci) for resistance to both diseases, which could be confirmed here, and at least four additional QTLs identified by using mapping populations on four generations. The introgression germplasm developed here will extend the useful genetic diversity of the primary gene pool by providing novel wild resistance genes against these two destructive peanut diseases.